BRD4 inhibitor and histone deacetylase inhibitor synergistically inhibit the proliferation of gallbladder cancer in vitro and in vivo. Issue 8 (11th July 2019) - Liu, Shilei; Li, Fengnan; Pan, Lijia; Yang, Ziyi; Shu, Yijun; Lv, Wenjie; Dong, Ping; Gong, Wei
Abstract: Gallbladder cancer (GBC) is the most common malignancy of the bile duct and has a high mortality rate. Here, we demonstrated that BRD4 inhibitor JQ1 and histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) synergistically inhibited the GBC cells in vitro and in vivo. Our results showed that cotreatment with JQ1 and SAHA significantly inhibited proliferation, cell viability and metastasis, and induced apoptosis and G2/M arrest in GBC cells, with only minor effects in benign cells. In vivo, tumor volumes and weights of GBC xenograft models were significantly decreased after treatment with JQ1 or SAHA; meanwhile, the cotreatment showed the strongest effect. Further study indicated that the above anticancer effects was associated with the downregulation of BRD4 and suppression of PI3K/AKT and MAPK/ERK pathways. These findings highlight JQ1 and SAHA as potential therapeutic agents and their combination as a promising therapeutic strategy for GBC. Abstract : We demonstrated JQ1 and SAHA to be potential therapeutic agents and their combination as a promising therapeutic strategy for gallbladder cancer.